Simulasi Diskrit untuk Pengaturan jumlah Gate pada Commuter Line Jabodetabek Rute Perjalanan Bogor - Jakarta Kota - Winnie Septiani; Pudji Astuti; Fitria Helmanila (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2016)
The purpose of the present study is to to develop discrete simulation models for setting thenumber of gate entry and exit gate in the e-ticketing system commuter Jabodetabek travel route Bogor -Jakarta Kota. Discrete event that occurred in the queue gate entrance and exit gate of which is the Linecommuter passenger arrival in the gate entrance and exit gate and passenger service level in the system.Based on the analysis of passenger and utility ratio of gates at 24 station, there were four groups ofstations and four groups of the time. The performance evaluation system was based on: number ofpassengers in the system (LS), the number of passengers in the queue (Lq), waiting time in the system(Ws) and the waiting time in the queue (Wq) used a software application program WinQsb QueuingAnalysis. Results of the evaluation of the proposal setting the number of gate entry and exit gate showedutility value higher than the previous condition. The proposal was expected to improve the effectiveness ofe ticketing system commuter JabotabekKeywords: commuter line, dicrete simulation, e-tocketing system, number of gate, utilities